Social workers' judgments: Case study on personal experience, professional training, and practice environment. (March 2022) - Kwan, Chi Kin; Chui, Ernest Wing Tak
Given the vital basis of the professional judgments made by social workers, this article proposes a framework with which to study the complex mechanisms involved in their judgments that considers three Ps: personal experience, professional training, and practice environment. Using a qualitative case study analysis, the authors apply the framework to examine the experiences of 20 Chinese social workers based in Hong Kong. Three cases have been selected to illustrate three trajectories as revealed from the 20 cases. Consistent with the notion of reflective practice, the analysis enhances the understanding of the forces behind the judgments that social workers make.